“Manejo y prevención de Cochinilla (Pseudococcus sp.) en el racimo de banano en la hacienda María José 1, zona de Babahoyo.” - Melendez Vergara, Gladys Gisella (2019)
VII. SUMMARY Banana is a Musaceae, perennial with a rapid development and can be harvested all year round. Integrated pest management is a viable alternative that is defined as the rational application of a combination of biological and chemical measures, so that the use of phytosanitary products allows the population of insect pests to be maintained at lower levels. In the María José 1 farm the cochineal in the banana cluster is a plague that affects the economic and commercial. Normally the cochineal is visible in winter, because it rises to the plant due to excess moisture in the soil and in the case that there is no good cultural control in the plantation, the clusters would be affected. To detect the presence of this pest, the phytosanitary department of the María José 1 farm carries out samplings, which are taken at random, where upon detection of an area with cochineal, the degree of affectation is estimated. The parameters that the Dolé technicians measure are the proximity of the insect pest to the cluster, population by control point, and the correct cultural control that is being applied in the plantation. In the haciendas monitored by the exported banana Dolé organic or chemical products are applied when there are severe attacks of cochineal, usually use potassium soap and is applied with a cp3 pump where the pseudostem is specifically fumigated, it can also be done with 200 gr of detergents in 20 ltrs of water and 10 cc of chlorine. Carlos Carrasco inspector of quality detailed that, when being cut the cluster, before being processed and exported these pass through several filters of quality in order to find any defect either by plague or manipulation of the fruit. At present, the María José 1 farm that cuts fruit for the Dolé exporter keeps this pest insect under control due to its compliance with the exporter's requirements and the good agricultural practices of Banana Keywords: Cochineal, Banana, Control, Prevention, Pest, Quarantine.